Haemorrhage in the course of subcardial gastrointestinal stromal tumour – a case description - Pedowski, Tomasz; Pedowska, Marlena; Masiak, Wioletta; Ciechański, Aleksander; Ćwik, Grzegorz; Dąbrowski, Andrzej; Wallner, Grzegorz (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
This paper is a discussion of the case of a 51-year-old female patient admitted urgently for haemorrhage from the upper gastrointestinal tract and increased dysphagia. After preliminary treatment, the patient was qualified for surgery, during which a large lesion was discovered in the shape of a stromal tumor closely connected with the oesophago-gastric junction. A resection of the tumor and part of the oesophagus was carried out, and a cervical fistula was formed. After a 4-month period, the continuity of the gastrointestinal tract was restored by forming a substitute organ out of the ascending colon and the end of the small intestine, anastomosed on the cervix. The patient was discharged in good overall condition.